Splenogonadal fusion: a case report of three cases and a literature review - Luo, Na; Xu, Qitao; Wang, Hao; Su, Jiahong; Li, Shoulin (Frontiers in Pediatrics, 2024)
To further the understanding of clinical physicians regarding spleno-gonadal fusion (SGF) and to help them consider SGF as a differential diagnosis when testicular tumors are reported, thus avoiding unnecessary orchiectomies.We reported 3 cases of SGF admitted to our hospital, including one suspected testicular tumor. We searched the literature on scrotal masses in the past 25 years and summarized the characteristics of SGF manifested as scrotal swelling combined with our cases.Results: After conducting a thorough search, we found that there were a total of 24 literary works related to this case, which included 25 testes. All lesions were located on the left side, and the average age of those affected was 20.22 years. Seven cases were continuous type.Three cases presented with pain, all of which were intratesticular masses. Thirty cases had a definite onset duration, ranging from 3 weeks to 10 years. Nine cases (36%) underwent orchiectomy, and 1 underwent partial orchiectomy.It is crucial to identify SGF in the clinic. When a patient manifests scrotal swelling, diagnosing SGF pre-operatively is challenging, and it should be considered when there is a long history of a stable testicular mass. We should perform an intraoperative frozen section if a testicular tumor is suspected in case of unnecessary orchiectomy.